Treatment of Infrabony Defects by Open Flap Debridement with or without Diode Laser - Agrawal, S.; Pradhan, S. (Kathmandu University Medical Journal, 2022)
Background Periodontitis is the common oral condition which affects the periodontium of the teeth that leads to destruction of periodontal ligaments and alveolar bone. Open flap debridement is the surgical procedure which provides access and visibility of the site, application of laser as an adjunct has various advantages. Objective To compare clinical outcomes after open flap debridement with or without diode laser. Method Patients aged 25-45 years diagnosed with infrabony defect ≥ 5 mm visiting Department of Dental Surgery, Bir Hospital. Control group sites were treated with open flap debridement alone, whereas test-groups were treated with Open flap debridement with diode laser. Various parameters like Plaque index, Gingival index, Pocket depth and Clinical attachment level were assessed and compared between groups at baseline, 3 and 6 months. Result The mean plaque and gingival scores improved in both the control and test groups at 3 and 6 months follow up as compared to baseline and was statistically nonsignificant between two groups. Open flap debridement with or without diode laser in the treatment of periodontal intrabony defects did not produce significant reduction in pocket depth and gain in clinical attachment level. Conclusion There was no significant differences in the clinical parameters were seen in the surgical flap debridement of infrabony pocket with and without diode laser. Diode laser can be used safely as an adjunct. However, long-term, multicentric, histologic and microbial studies are required.